Relation between cell-to-cell adhesion and angiogenesis and clinico-morphological prognostic factors in patients with gastric cancer - Bazas, V.M.; Lukyanova, N.Yu.; Demash, D.V.; Galakhin, K.O.; Myasoedov, D.V. (Experimental Oncology, 2008)
To study the relation between the expression of the molecules of cell-to-cell adhesion (Е-cadherin, a- and b-catenins) and vascular endothelial growth factor (VEGF) and traditional clinico-morphological characteristics of tumors to evaluate their prognostic value in the patients with gastric cancer. Methods: To analyze the expression of Е-cadherin, a- and b-catenins, and VEGF the paraffin embedded tumor samples were studied by immunohistochemical analysis with the use of respective monoclonal antibodies. Results: The presence of E-cadherin in tumors correlated with the absence of metastases in regional lymph nodes and was observed, as a rule, in the patients at the early stages of the disease. The presence of b-catenin expression has been detected in gastric tumors of the patients without distant metastases, while the level of VEGF expression correlated with the degree of gastric wall injury. It has been demonstrated that the expression of E-cadherin and a-catenin is associated with favourable disease course and is a characteristic pattern for early stages of gastric cancer of intestinal type. However, VEGF expression is typical for the late stages of gastric cancer of diffuse type and is associated with poor prognosis. Conclusion: At the base of combined clinical, histological and immunohistochemical analysis of gastric tumors it has been shown that E-cadherin, a-catenin and VEGF could be used as informative markers of the disease course.